The two decisive (but insufficient) steps of the Council of Europe and the European Union: two decisive (but insufficient) steps of the Council of Europe and the European Union - Díaz Galán, Elena C. (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
This paper examines the most notable developments in the regulation of Artificial Intelligence (AI) on the European continent, through the two key European organizations: The Council of Europe adopted “The Framework Convention on Artificial Intelligence”; and the European Union adopted the “EU Artificial Intelligence Act” which is a European regulation on this field, both of 2024. These two instruments are vital to understanding the legal regulation of this matter in Europe as well as in much of the international community. The study of these norms provides useful conclusions for understanding the details of AI legal regulation, being Europe a pioneer in regulating it.
Keywords: fundamental rights; rule of law; ethical principles; human supervision; sanctions